Food processing industry energy and water consumption in the Pacific northwest. (June 2018) - Compton, Marc; Willis, Sarah; Rezaie, Behnaz; Humes, Karen
Abstract: The food processing industry is one of the largest consumers of energy and water in the manufacturing sector. It is vital that conservation measures are taken to reduce the use of electricity, fuel, and water for producers to have long-term, sustainable growth. The Pacific Northwest (PNW) region includes some the largest food processers in the United States, particularly with products such as fruit and vegetable preserves, apples products, potato products, and milk. Energy and water consumption in PNW food processing facilities are quantified as well as techniques to increase efficiency and reduce waste. Mechanical drive systems and refrigeration consumes the most electricity in the industry and the implementation of energy management plans has the largest potential to save electricity in PNW facilities. Heating and cooling process needs are the largest consumers of energy in the food processing industry. Implementing cogeneration/trigeneration technology, replacing of older equipment, capturing waste heat, and reusing wastewater can have significant impacts on both energy and water consumption. Novel, emerging technologies such as membrane separation, high-pressure processing, microwave assist, ultrasound, pulsed high electric fields, ozone, and hydrogen/electricity generation have significant potential to benefit the food processing industry by increasing efficiency and allowing companies to stay competitive in an industry where sustainable practices are becoming increasingly important to the public. Highlights: Energy consumption in food processing industry in Pacific Northwest is mapped. Water consumption in food processing industry in Pacific Northwest is mapped. Methods and technologies for reduction energy consumption in the food industry are summarized. Methods and technologies for reduction water consumption in the food industry are summarized.